Recent Advances in Monoclonal Antibody Therapies for Multiple Sclerosis - Wootla, Bharath; Watzlawik, Jens O; Stavropoulos, Nikolaos; Wittenberg, Nathan J; Dasari, Harika; Abdelrahim, Murtada A; Henley, John R; Oh, Sang-Hyun; Warrington, Arthur E; Rodriguez, Moses (Expert opinion on biological therapy, 2016)
INTRODUCTION: Multiple sclerosis (MS) is the most common chronic inflammatory, demyelinating disease of the CNS and results in neurological disability. Existing immunomodulatory and immunosuppressive approaches lower the number of relapses but do not cure or reverse existing deficits nor improve long-term disability in MS patients. AREAS COVERED: Monogenic antibodies were described as treatment options for MS, however the immunogenicity of mouse antibodies hampered the efficacy of potential therapeutics in humans. Availability of improved antibody production technologies resulted in a paradigm shift in MS treatment strategies. In this review, an overview of immunotherapies for MS that use conventional monoclonal antibodies reactive to immune system and their properties and mechanisms of action will be discussed, including recent advances in MS therapeutics and highlight natural autoantibodies (NAbs) that directly target CNS cells. EXPERT OPINION: Recent challenges for MS therapy are the identification of relevant molecular and cellular targets, time frame of treatment, and antibody toxicity profiles to identify safe treatment options for MS patients. The application of monoclonal antibody therapies with better biological efficacy associated with minimum side effects possesses huge clinical potential. Advances in monoclonal antibody technologies that directly target cells of nervous system may promote the CNS regeneration field from bench to bedside.
Keywords: Multiple Sclerosis; monoklonální protilátky; Immunotherapy; Immunosuppressive Agents; imunoterapie; zvířata; imunosupresiva; Antibodies, Monoclonal; Humans; tvorba protilátek; roztroušená skleróza; Antibody Formation; lidé; Animals